A method for measuring the amount of hoar frost formation in the recuperation channels of ventilation systems using the adjustable mathematical model of this process; MATEC Web of Conferences; Vol. 141 : Smart Grids 2017 - Shilin A. A. Aleksandr Anatoljevich; Prokhorov S. Sergey; Shabo A. Andrei; Bukreev V. G. Viktor Grigorievich (2017, 2017)
Title screen